Wholegrains and health: Many benefits but do contaminants pose any risk?. Issue 2 (29th April 2019) - Nugent, A. P.; Thielecke, F.
Abstract: Since pre‐historic times, humans have consumed grains as part of their diet. Being rich in carbohydrates, grains typically form a key part of all food‐based dietary guidelines, with wholegrains recommended as healthy dietary choices. However, grains are also exposed to contaminants from air, soil, water, insects, animals, microbes, humans, storage and shipping containers, and handling and processing equipment and can be one of the main dietary sources of food‐borne contaminants by virtue of their frequent consumption. Recent scientific reports positively highlight wholegrains as foods with inherent health properties, which, because they provide fibre and micronutrients such as B vitamins and zinc, can improve the quality of carbohydrate intake as part of sustainable, healthy diets. This article describes potential health‐protective properties inherent to wholegrains and contends that the presence of contaminants in wholegrains, including mycotoxins, heavy metals and acrylamide, merits continued monitoring but that any such risk does not outweigh the known benefits of wholegrain consumption.